Gamification as a Pedagogical Strategy for Religious Moderation: Evidence from a Quasi-Experiment on Generation Z Students - Umi Liwayanti; Ratih Widya Nurcahyo; Febrianto Sabirin; Dewi Sulistiyarini; Norazila binti Abdul Talip (FKIP Universitas Lampung, 2026)
Religious moderation is an essential competency for Generation Z students to maintain social cohesion in the digital era. Despite this importance, students may demonstrate tolerant dispositions without strong conceptual literacy. This study examined the effectiveness of gamification in Islamic Religious Education (IRE) as a strategy to strengthen the internalization of religious moderation by improving both religious moderation knowledge (MK) and religious moderation attitude (MA). The study employed a quasi-experimental, non-equivalent control group design involving 128 undergraduate students at Universitas PGRI Pontianak (experimental group, n = 63; control group, n = 65). MK was measured using a knowledge test, and MA was assessed using an attitude questionnaire. Data were analyzed using descriptive statistics and multivariate analysis of covariance (MANCOVA), with pretest scores treated as covariates. Descriptive findings showed that MA increased from high to very high in both groups (control: M = 59.28 to 70.92; experimental: M = 58.86 to 73.43). MK also increased from very low to high (control: M = 43.08 to 71.54; experimental: M = 42.30 to 78.49). After controlling for baseline scores, the multivariate analysis indicated a significant group difference on the combined outcomes (p < .001) with a very large effect size (partial η² = 0.543). Follow-up univariate tests confirmed significant effects of gamification on MK (p < .001; partial η² = 0.508) and MA (p < .001; partial η² = 0.255), indicating that the gamified class achieved higher posttest outcomes than the control class. These results suggest that gamification is a promising strategy for IRE learning in the digital era because it supports conceptual mastery of moderation while also strengthening moderation attitudes among Generation Z students. Keywords: gamification, religious moderation, islamic religious education, generation Z students.